Teacher Leadership Development: The Role of Professional Certification Programs - Bilash Mallik (Scientia Publica Media, 2024)
The past few decades have seen a growing interest in teacher leadership development worldwide. However, there is a need for more empirical research to understand how professional certification programs make teachers leaders, what roles teacher leaders play and what challenges they encounter. This study addresses these questions by examining the perceptions of eight professionally certified teachers working at a Government College in Bangladesh. As a qualitative study, participants were selected through purposive and snowball sampling, and a self-developed semi-structured interview schedule was used to collect the data. Data were then analyzed thematically. The findings reveal that professional certification programs significantly contribute to making teachers as leaders, enhancing their pedagogical, professional, research, and collaborative skills compared to their prior positions. In addition, these professionally certified teacher leaders motivate students for better careers and organize seminars, symposiums, and workshops to improve their achievement, inspire colleagues to pursue higher degrees, exchange innovative teaching approaches with them for their professional development, and work on academic committees and research cells, provide valuable insights for overall college improvement. However, the study found that professionally certified teachers face challenges such as a top-down leadership approach, a lack of collaborative college culture, external political pressure, limited financial incentives for pursuing degrees, and a lack of desirable postings to complete the professional certification programs. In contrast to previous literature, the study did not find a lack of time among the professionally certified teachers to perform leadership roles. This study sheds new light on developing teacher leadership through professional certification programs and providing insights for principals and policymakers on how certified teachers contribute to overall college improvement. Future research should focus on the impact of teacher professional certifications on student achievement, colleagues’ professional development, and overall college improvement from students’, colleagues’ and principals’ perspectives.